Performance Comparison of Point-to-Point and Point-to-Multipoint Fiber Optic Networks Using QoS Parameters and the Analytical Hierarchy Process (AHP) - Husni Husni; Taufiq Taufiq; Defry Hamdhana; Muhammad Daud; Asrianda Asrianda (Journal of Applied Informatics and Computing, 2026)
The rapid growth of internet traffic in Indonesia, including in Aceh Province, requires an optical fiber network infrastructure that is both efficient and reliable. Two fundamental architectures, Point-to-Point (P2P) and Point-to-Multipoint (P2MP), offer different trade-offs between service quality and cost efficiency, yet a quantitative comparison that combines Quality of Service (QoS) measurement with a structured multi-criteria decision-making method remains limited. This study experimentally measures the throughput, delay, jitter, packet loss, and bandwidth of P2P and P2MP networks implemented at Universitas Almuslim, Bireuen, Aceh, using iPerf3 and Wireshark under varying client loads of 1, 2, 4, 8, and 16 users, and applies the Analytical Hierarchy Process (AHP) to weight the QoS criteria and rank the two architectures. The results show that P2P consistently outperforms P2MP on every QoS parameter, maintaining an average throughput of 95 Mbps, a delay of 2.68 ms, a jitter of 0.85 ms, a packet loss of 0.054%, and a fixed bandwidth of 100 Mbps, whereas P2MP degrades progressively as the number of users increases. AHP weighting identified throughput as the most influential criterion (0.50), followed by bandwidth (0.26), delay (0.13), jitter (0.07), and packet loss (0.03), with a Consistency Ratio of 0.054, confirming that the pairwise judgments were consistent. The resulting AHP scores were 9.00 for P2P and 2.66 for P2MP, indicating that P2P is the more optimal architecture for QoS-sensitive deployments, while P2MP remains advantageous where cost efficiency and wide coverage are prioritized.